Pertanggungjawaban Oknum Polisi yang Melakukan Penganiayaan Terhadap Tersangka dalam Proses Penyidikan (Studi Kasus Putusan Nomor 7/PID/2016/PT BBL) - Mufti, Muhammad Wildan (Jurnal Hukum Statuta, 2023)
This study analyzes the accountability of police officers who commit acts of violence against suspects during the investigation process, with a case study based on decision number 7/PID/2016/PT BBL. This case involves four officers from the Narcotics Unit of the Bangka Police Resort who inflicted violence on a drug suspect, resulting in the suspect's death. Such actions violate human rights and damage the reputation of the police. The study aims to analyze the legal protection available to suspects who are victims of police violence and to identify the enforcement of law against police officers involved in violence during investigations. A normative legal method is employed using both statute and conceptual approaches. The findings indicate that although there are regulations protecting suspects' rights, police violence still occurs, and the enforcement of law against perpetrators of violence is often inconsistent. There is a need for enhanced human rights training for police officers, strengthened oversight mechanisms, and active community participation in reporting violence. These measures are expected to improve the integrity and public trust in law enforcement in Indonesia.